Affinity monolith chromatography: A review of general principles and applications. Issue 22 (22nd May 2017) - Li, Zhao; Rodriguez, Elliott; Azaria, Shiden; Pekarek, Allegra; Hage, David S.
Abstract: Affinity monolith chromatography, or AMC, is a liquid chromatographic method in which the support is a monolith and the stationary phase is a biological‐binding agent or related mimic. AMC has become popular for the isolation of biochemicals, for the measurement of various analytes, and for studying biological interactions. This review will examine the principles and applications of AMC. The materials that have been used to prepare AMC columns will be discussed, which have included various organic polymers, silica, agarose, and cryogels. Immobilization schemes that have been used in AMC will also be considered. Various binding agents and applications that have been reported for AMC will then be described. These applications will include the use of AMC for bioaffinity chromatography, immunoaffinity chromatography, dye‐ligand affinity chromatography, and immobilized metal‐ion affinity chromatography. The use of AMC with chiral stationary phases and as a tool to characterize biological interactions will also be examined.